Transformation of Strategic Management Accounting to Support Innovation and Competitive Advantage in the Digitalization Era - Pasaribu, Hiras; Ghozali, Zein; Susilawati, Made; Masnoni, Masnoni (PT. Anagata Sembagi Education, 2025)
Strategic management accounting transformation is becoming increasingly important in the era of digitalization, where companies are required to adapt to technological developments in order to improve efficiency, innovation, and competitiveness. This research aims to analyze how strategic management accounting transformation can support innovation and competitive advantage in the digitalization era. In addition, this research also identifies challenges and success factors in the implementation of digital technology in strategic management accounting. The research method used is a qualitative approach with a case study method in several companies that have implemented digital-based strategic management accounting. Data were collected through in-depth interviews with finance managers, strategy managers, and innovation teams, as well as observations of the implementation of digital technology in the accounting system. Data analysis was conducted using thematic and comparative approaches to identify the main patterns in the transformation of strategic management accounting. The results show that digitization in strategic management accounting improves operational efficiency, transparency of financial information, and supports innovation by providing more accurate and real-time financial data. However, the study also identified key challenges in this transformation, such as employee resistance to technological change and high investment costs. In addition, top management support and human resource readiness are key factors in the successful implementation of digital technology in strategic management accounting. The implications of this study suggest that companies looking to improve competitiveness through digital transformation in management accounting need to invest in technology, employee training, as well as the development of policies that support innovation.